Hyperbaric oxygen alleviates the activation of NLRP-3-inflammasomes in traumatic brain injury - Qian, Huihui (Mol Med Rep, 2017)
Growing evidence has demonstrated that the nucleotide-binding oligomerization domain-like receptor family pyrin domain containing 3 (NLRP-3) inflammasome-mediated inflammatory pathways have been involved in the secondary injury of traumatic brain injury (TBI). In the present study, the authors investigated the effects of hyperbaric oxygen (HBO) therapy on the NLRP-3 inflammasome pathway following TBI. Following the evaluation of motor deficits and brain edema, the therapeutic effects of HBO on interleukin (IL)-1β and IL-18 expression were assessed, as well as NLRP-3 inflammasome activation following TBI. HBO may improve motor score and reduce brain edema, accompanied with the reduction of IL-1β and IL-18 during the 7-day observation period. Furthermore, HBO suppressed mRNA and protein expression of NLRP-3-inflammasome components, especially reducing NLRP-3 expression in microglia. Thus, these results suggested that HBO alleviates the inflammatory response in experimental TBI via modulating microglial NLRP-3-inflammasome signaling.